Public Awareness of Risks Associated with Alcohol Drinking in the US: A Population-Based Cross-Sectional Survey Study - Ofei-Dodoo, Samuel; Okut, Hayrettin; Dogbey, James (Kansas Journal of Medicine, 2025)
Introduction. Alcohol consumption is a leading preventable cause of morbidity and mortality in the United States, contributing to over 178,000 deaths annually. Despite known links to liver disease and cancer, few adults report receiving counseling on alcohol-related risks from health care professionals. Authors of this cross-sectional, population-based study assessed the prevalence of alcohol-related counseling among United States adults and identified sociodemographic and behavioral factors associated with receiving such advice. Methods. Data were drawn from the 2022 Health Information National Trends Survey, a nationally representative sample of United States adults. The primary outcome was whether respondents reported receiving information from a health care professional about the negative health risks of alcohol use, including specific negative health consequences. Survey-weighted univariate, bivariate, and multivariable logistic regression analyses were used to identify predictors of receiving counseling. Results. Only 26.1% of respondents reported receiving alcohol-related counseling, and just 10.9% specifically were informed about liver disease. Multivariable analysis showed higher odds of counseling among adults aged 18-34 (OR = 2.43; 95% CI, 1.84-3.21), non-Hispanic Black respondents (OR = 1.45; 95% CI, 1.20-1.75), those with income under 20,000 (OR = 1.27; 95% CI, 1.02-1.59), and individuals consuming more than one alcoholic drink per week (OR = 1.40; 95% CI, 1.22-1.61). Lower odds were found among women (OR = 0.67; 95% CI, 0.59-0.77), and those worried about cancer (OR = 0.81; 95% CI, 0.67-0.96). Conclusions. Findings highlight important gaps and disparities in alcohol-related counseling. Standardized interventions and improved outreach are needed to align prevention efforts with patient risk.